1995
DOI: 10.1159/000126986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacterial Endotoxin and Interleukin-1 on Prostaglandin Biosynthesis by the Hippocampus of Mouse Brain: Role of Interleukin-1 Receptors and Glucocorticoids

Abstract: There is increasing evidence indicating that the production of cytokines and prostaglandins (PG) may be interrelated and is regulated by glucocorticoids (GC). In the present study we examined the effect of the bacterial endotoxin lipopolysaccharide (LPS) and interleukin-1 (IL-1) on the ex vivo production of PGE2 by the dorsal hippocampus of the mouse which contains high levels of receptors to IL-1. The roles of IL-1 receptors and GC in the regulation of LPS- or IL-1-induced PGE2 productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Systemically administered a-MSH reduces cytokine expression in cerebral ischemia (Huang & Tatro 2002) and in brain inflammation induced by LPS (Rajora et al 1997). a-MSH was shown to inhibit PGE 2 release induced by LPS or IL1b from hippocampal fragments (Weidenfeld et al 1995) but not from hypothalamic fragments (Mirtella et al 1995). However, we reported that melanocortins inhibit the production of NO and PGs induced by IL1b in rat hypothalamus (Cragnolini et al 2006).…”
Section: Mc4r and Inflammationmentioning
confidence: 65%
“…Systemically administered a-MSH reduces cytokine expression in cerebral ischemia (Huang & Tatro 2002) and in brain inflammation induced by LPS (Rajora et al 1997). a-MSH was shown to inhibit PGE 2 release induced by LPS or IL1b from hippocampal fragments (Weidenfeld et al 1995) but not from hypothalamic fragments (Mirtella et al 1995). However, we reported that melanocortins inhibit the production of NO and PGs induced by IL1b in rat hypothalamus (Cragnolini et al 2006).…”
Section: Mc4r and Inflammationmentioning
confidence: 65%
“…α-MSH is a potent inhibitor of the induction of iNOS in cultured macrophages and NO production in liver and microglia [4, 17, 19]. Also, α-MSH was found to inhibit PGE 2 production in brain tissue [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Since it has been shown that HPA axis responses to certain immune and stressful stimuli are inhibited in adrenalectomized (Adex) rats [11, 12], we examined whether circulating GC are required for the ACTH response to HSV-1 inoculation. Table 1 shows that in contrast to sham-operated rats, in Adex-rats HSV-1 inoculation did not cause an increase in serum ACTH levels above those found in vehicle-treated animals.…”
Section: Resultsmentioning
confidence: 99%